A Study on Green Human Resource Management Practices in Jaffna - Thasika, Y.; Dilogini, S.; Nishanthini, A. (University of Jaffna, 2016)
Using exploratory study, the pervading nature of green human resource management practices was examined in organizations located in the Jaffna district. The data were garnered from human resource practitioners by using in-depth interviews with open ended questions. Collected data were coded and subsequently themes were subsumed under recruitment, training and development, performance evaluations, and reward management. The majority of the informants interviewed connoted that the green human resource management practices have not received magnificent attention in the past nonetheless, those practices were found at burgeoning stage. The informants were well aware of the importance of the green human resource management practices and its implication of their businesses. This research would be a springboard for future research scholars.
Keywords: Green HRM practices; Organizations; Green team